Analisis Efisiensi Generator Pada GT21 Blok 2 Pembangkit Listrik Tenaga Gas Dan Uap PT. CEPA Sengkang - AR, Ashar; Hamma, Hamma; Alfira WS, Wisna Saputri; Asri, Andarini; Ardiyansyah, Ardiyansyah (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
PLTGU Sengkang which is operated by PT. CEPA Sengkang with a total capacity of 315 MW. One of the important components in the PLTGU system is a generator. In a generator there are many problems that arise, including generator efficiency problems. The research that will be carried out is to determine the generator efficiency value and then determine how much the generator efficiency value increases. In finding the efficiency value by making daily and monthly loading curves using generator output power, generator input power data, generator nameplate and generator power losses at 25%, 50%, 75%, and 100% loading. In this study, taking a sample that lasted for 1 month (31 days) of generator efficiency data for each loading and comparing the actual with the generator specifications, the difference for loading 25% experienced a decrease in efficiency of 0.35%, for loading 50% experienced an efficiency increase of 0.12%, for loading 75% increased efficiency of 0.25% and for loading 100% increased efficiency of 0.32%. In this study the generator has experienced reverse power so that the efficiency of the generator has decreased. The average efficiency in May 2022 was 96.21%, with an average load of 29.96 MW and an average input power of 31.14 MW. Referring to the manual book Block 2 PLTGU PT. CEPA Sengkang is known that the generator efficiency value is by design divided into 4 loadings. For loading 25% efficiency is 96.6%, for loading 50% efficiency is 98.45%, for loading 75% efficiency is 98.82%, and for loading 100% efficiency is 98.93% and so that the optimum efficiency of the generator occurs at a load of 54.2 MW (loading 100 %) with a value of 99.62%.